STUDY THE UNIFORMITY OF CONNECTING TISSUE FORMING INSTEAD BIODEGRADABLE IMPLANT IN EXPERIMENT WITH ANIMALS - Игорь Александрович Эйзенах; Натиг Ариф Оглы Абдуллаев; Владимир Анатольевич Осташевский; Вадим Гельевич Мозес; Кира Борисовна Мозес; Михаил Юрьевич Солуянов (Медицина в Кузбассе)
Aim – study by statistic tests the uniformity of connecting tissue forming instead biodegradable polymer, made by electrospinning, in experiment with animals.